Monotypic no more: A new species of the unusual genus Mayagueza Wheeler, 1960 from the Neotropical region (Diptera: Drosophilidae: Steganinae) - Costa, Sávio Cunha; Pirani, Gabriela; Oliveira, Sarah Siqueira (Zootaxa, 2021)
A new species belonging to the previously monotypic steganine genus Mayagueza Wheeler, 1960 (Diptera: Drosophilidae) is described. The new species, Mayagueza lopesi sp. nov., was collected in the Brazilian Cerrado. This is the first record of this genus for South America, and the description of the new species, based on male and female adult specimens, includes photographs and detailed illustrations of male and female terminalia.